Developing a Car Park with Introducing Interlocking Concrete Block at INTI International University - G., Ravinthiran (2015)
This project is mainly about developing car park with introducing interlocking concrete block at INTI international university. The purpose of my project is to create a greener environment around campus. The work has been done with collecting some literature view based on topic. In this project there are few section been divided: The first section is introduction where introduces briefly about interlocking concrete block as well as the purpose and objective of this project. The second section is about advantages and the limitation of interlocking concrete block consists of studies about concrete blocks. The next section will shows about the types of interlocking concrete block and characteristics of interlocking concrete block and physical requirements. A survey form has been created to investigate the perception of the road users towards the use of interlocking concrete block around campus. The fourth, which is the most important section of this project, is developing car park with introducing interlocking concrete block. After all the researches and studies, this section will show the methods and techniques how to develop car park with interlocking concrete block. A calculation of the number of concrete block needed. With collected data, the estimation of the paving cost being calculated. The car park area was calculated using the JKR method which follows the specific standard measurements of Malaysia. The fifth section is conclusion where concludes the report with the final information and results obtained. The last section is references which show all the books and website links used as references to study and researches for my project.